Investigation of biomarker properties of DARS2 to distinguish squamous cell carcinoma from keratoacanthoma - Ucer, Ozlem; Kocaman, Nevin (Annals of Medical Research, 2022)
Aim: This study was aimed at investigating the effectiveness of DARS2 protein expression in the differential diagnosis of squamous cell carcinoma (SCC) and keratoacanthoma (KA).Materials and Methods: A total of 60 cases, 30 SCC and 30 KA, diagnosed in the Fırat University, Faculty of Medicine, Department of Pathology, were analysed immunohistochemically by studying the DARS2 protein.Results: DARS2 expression values were found to be statistically significant in the differential diagnosis of SCC and KA (p
Keywords: Squamous cell carcinoma; Keratoacanthoma; Immunohistochemistry; DARS2